Myoepithelial carcinoma of the parotid gland: A case of adequate fine-needle aspiration cytology specimens rendering a conclusive diagnosis possible - Xin Guo; Jiro Watanabe; Sanae Ariyasu; Yasuyuki Sasaguri; Nozomu Kurose; Kei Fukushima; Sohsuke Yamada (SAGE Open Medical Case Reports, 2018)
An 80-year-old male presented with a history of a hard right parotid mass that had gradually increased in size, with subsequent facial paralysis. A fine-needle aspiration biopsy was performed. The cytologic specimens contained a substantial number of sheet-like clusters or small groups of a mixture of plasmacytoid, oval to spindled, or large epithelioid cells having hyperchromatic pleomorphic nuclei, abundant cytoplasm with occasional inclusion body-like materials, and prominent nucleoli, in a relatively clear background. We first interpreted it as a carcinoma, suggestive of myoepithelial differentiation. Radical parotidectomy was performed, and a gross examination of the neoplasm revealed a non-capsulated and ill-defined tumor lesion, with a grayish or yellowish cut surface, associated with fat invasion. On a microscopic examination, the tumor was predominantly composed of the solid proliferation of atypical cells including a mixture of oval to spindled, plasmacytoid, or epithelioid cells, often arranged in a trabecular and reticular growth pattern with patchy eosinophilic hyalinized stroma. Immunohistochemistry showed that the carcinoma cells were specifically positive for p63, cytokeratins, and vimentin. Finally, electron microscopy demonstrated that their phenotype was consistent with a myoepithelial origin containing many bundles of variably thin actin filaments. Therefore, we finally made a diagnosis of myoepithelial carcinoma, defined as the malignant counterpart of benign myoepithelioma. We should be aware that owing to its characteristic cytological features, cytopathologists may be able to make a correct diagnosis of myoepithelial carcinoma, based on multiple and adequate samplings.